Preliminary Characterisation of Sardinian Red Grape Cultivars (Vitis vinifera L.) According to Their Phenolic Potential - Vacca, V.; Del Caro, A.; Milella, G.G.; Nieddu, G. (South African Journal of Enology and Viticulture, 2016)
Fourteen cultivars and clones, mainly selected from the island of Sardinia (Italy) and grown in a collection field, showed significant quantitative differences in phenolic potential. An extraction method designed to reproduce the winemaking process was used to determine the amounts of extractable polyphenols, anthocyanins, catechins and proanthocyanidins reactive to vanillin, and the proanthocyanidins in grape skins and seeds. The Sardinian cultivar Nieddera and the Spanish cultivar Graciano had the highest concentrations of extractable polyphenols, anthocyanins, catechins and proanthocyanidins reactive to vanillin. Four clones of the Cannonau cultivar (synonym Grenache) exhibited fairly high variability, with significant differences in berry and seed phenolic contents.